2015
DOI: 10.1093/ejcts/ezv311
|View full text |Cite
|
Sign up to set email alerts
|

The combined role of sinuses of Valsalva and flow pulsatility improves energy loss of the aortic valve

Abstract: These findings (i) confirm the hypothesis that the sinuses of Valsalva play a key role in optimizing the aortic haemodynamics during systole, minimizing energy losses; (ii) suggest that the sinuses of Valsalva are needed because of the complex nature of blood flow during ejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…Fourdimensional magnetic resonance imaging, echo-particle image velocimetry, Doppler, and computational fluid dynamics can generate excellent flow visualizations, and many groups have studied the influence of sinuses on aortic root fluid dynamics. 5,[31][32][33][34][35][36][37][38][39][40] These studies clearly show that the sinuses of Valsalva critically influence the behavior of the aortic valve and root. Although we did not detect any meaningful differences in coronary blood flow, valve hemodynamics, or flow profiles between the conduits we compared, the benefits of neosinus creation might be overshadowed by the consequences of commissural distortion.…”
Section: Discussionmentioning
confidence: 68%
“…Fourdimensional magnetic resonance imaging, echo-particle image velocimetry, Doppler, and computational fluid dynamics can generate excellent flow visualizations, and many groups have studied the influence of sinuses on aortic root fluid dynamics. 5,[31][32][33][34][35][36][37][38][39][40] These studies clearly show that the sinuses of Valsalva critically influence the behavior of the aortic valve and root. Although we did not detect any meaningful differences in coronary blood flow, valve hemodynamics, or flow profiles between the conduits we compared, the benefits of neosinus creation might be overshadowed by the consequences of commissural distortion.…”
Section: Discussionmentioning
confidence: 68%
“…In case of VSO, the use of tube graft with neo‐SV, mimicking the native structure and dynamics, should theoretically be able to affect valve durability since perturbations of the regular movements of opening and closure of the native aortic valve and alterations in flow dynamics may be avoided . SV were also demonstrated to have a key role in optimizing the aortic hemodynamics during systole, minimizing energy losses . In addition, Weltert et al using finite element computer‐assisted stress analysis were able to show that the use of a standard tubular graft can be linked to higher stress to coronary sutures, while using a graft with preformed SV could relieve stress on the coronary anastomoses, potentially decreasing the incidence of postoperative complications such as bleeding and late pseudoaneurysm formation .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the recreation of the sinuses of Valsalva (SV) during aortic VSO remains a matter of controversy. Despite solid experimental and in vivo evidence of the physiologic importance of the SV for aortic valve function, there are limited data comparing the outcome of patients undergoing VSO with and without SV reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in vitro studies also suggest that the sinuses of Valsalva (aortic sinus) play an important role in the regulation of the aortic hemodynamics. Pisani et al [32] and Salica et al [33] found that the presence of the sinuses of Valsalva increases the effective orifice area when the cardiac output increased, which helps minimize the flow energy loss during ejection.…”
Section: Introductionmentioning
confidence: 99%